Who was Jesus? - Morgan, Ellen, 1970- (Who was-- ?, 2015)
This addition to the Who Was--? series "presents young readers with a biography that covers what is known historically about Jesus and places in his life in the context of his world when Jerusalem was part of the Roman Empire. In an even-handed and easy-to-read narrative, this title--illustrated with eighty black-and-white drawings--also explains the early origins of Christianity and how it became a major religion"--